Kansas Land Prices and Cash Rental Rates - Langemeier, Larry N. (My University, 1994)
This farm management guide reports Kansas land prices from 1977-1994 and cash rental rates for 1979-1994. The data is meant to be useful to farm managers.
MF1100_1994_10
Keywords: MF1100; Economics; MF